Vitamin D deficiency predicts 30-day hospital mortality of adults with COVID-19 - Neves, Fabio Fernandes; Pott-Junior, Henrique; Santos, Sigrid de Sousa; Cominetti, Marcia Regina; Freire, Caio Cesar de Melo; Cunha, Anderson Ferreira da; Jordão Júnior, Alceu Afonso (Universidade Federal de São Carlos, 2022)
Several studies have shown conflicting results for the relationship between vitamin D deficiency and COVID-19 outcomes. Here, we aimed to evaluate whether plasma 25(OH)D levels predict mortality in adults admitted with COVID-19, considering potential confounders. Methods: We conducted a retrospective cohort study that included 115 adults (age 62.1 ± 17.6 years, 65 males) admitted to a Brazilian public hospital for severely symptomatic COVID-19. Subjects were classified into two groups according to their plasma levels of 25(OH)D: sufficiency ( 50 nmol/L) and the deficiency (<50 nmol/L). The diagnosis of COVID-19 was performed using real-time polymerase chain reaction (qPCR). In addition, direct competitive chemiluminescence immunoassay assessed serum 25(OH)D levels. Results: The all-cause 30-day mortality was 13.8% (95% CI: 6.5%e21%) in the group of patients with sufficient plasma 25(OH)D levels and 32.1% (95% CI: 14.8%e49.4%) among those with deficient plasma 25(OH)D levels. Cox regression showed that plasma 25(OH)D levels remained a significant predictor of mortality even after adjusting for the covariates sex, age, length of the delay between symptom onset and hospitalization, and disease severity (HR ¼ 0.98, 95% CI: 0.96e1.00; p ¼ 0.02). Conclusion: Vitamin D deficiency predicts higher mortality risk in adults with COVID-19.
Deficiência de vitamina D prevê mortalidade hospitalar em 30 dias de adultos com COVID-19
Keywords: COVID-19; SARS-Cov-2; vitamina d; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA